The Regulation of Digital Platforms and Freedom of Expression in Indonesia’s Constitutional System - Zahra Nabilla; Azka Syifaul Maula (Iustitia: Journal of Legal Theory, Politics, and International Relations, 2026)
This study examines the constitutional relationship between digital platform regulation and freedom of expression within Indonesia’s legal system by analyzing the normative imbalance between state moderation authority and constitutional protections of communicative liberty. The research employs a non empirical juridical methodology grounded in constitutional, doctrinal, conceptual, and comparative legal analysis through the examination of the Constitution of Indonesia 1945, the Electronic Information and Transactions Law, Ministerial Regulation Number 5 Year 2020, Constitutional Court decisions, and scholarly discussions concerning digital constitutionalism and democratic governance. The findings demonstrate that Indonesian digital regulation continues to prioritize administrative control, platform compliance obligations, and public order rationales without developing sufficiently coherent proportionality standards capable of protecting constitutional freedom of expression. Constitutional adjudication has recognized the significance of online participation within democratic society, yet judicial interpretation remains inconsistent in defining legality, necessity, procedural fairness, and restrictive limits applicable to digital expression regulation. The study argues that reconstruction of Indonesian digital governance requires rights based constitutional proportionality, transparent moderation mechanisms, independent oversight institutions, and stronger safeguards against disproportionate state intervention in digital communicative spaces.